A step-by-step guide to mastering research proposal writing / Mahmathi Karuppanan - Karuppanan, Mahmathi (Faculty of Pharmacy, 2024)
The online webinar, "Mastering Research Proposal Writing: A Step-by-Step Guide," was conducted on 23 November 2024, specifically for postgraduate students of the Master in Clinical Pharmacy and Master in Pharmacy Practice programs offered at the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Puncak Alam. The webinar aimed to guide participants through the essential steps of proposal writing, focusing on key components to help them develop well-structured, compelling, and ethically sound research proposals. This skill is particularly important for these students as they are currently at the proposal writing stage of their academic journey. The event was attended by 38 students.